Performance of Problem-Based Learning Based Image Teaching in Clinical Emergency Teaching - Xu, Xiaohong; Wang, Yingcui; Zhang, Suhua; Liu, Fengting (Frontiers in Genetics, 2022)
at present, with the rapid increase of emergency knowledge and the improvement of people's requirements for medical quality, the traditional teaching mode can not fully meet the needs of emergency teaching in the new era. This paper aims to improve the clinical emergency teaching mode by PBL teaching method, and improve the comprehensive ability of clinical emergency of medical students. This article proposes a problem-based PBL imaging teaching method, combining the characteristics and content of clinical emergency courses, focusing on students, highlighting the problem-solving process, and improving students' creative thinking ability. To cultivate students' interest in clinical learning, develop their self-learning ability, train their teamwork and communication skills, and cultivate their ability to set, question and solve questions, so as to promote medical students' overall comprehensive ability to integrate specialized knowledge and clinical practice.In this paper, the PBL teaching method and the traditional teaching method of comparative experiments show that the PBL teaching method can more effectively highlight the characteristics of clinical emergency medicine teaching mode, and make full use of the limited emergency teaching resources, so as to improve the quality of clinical emergency teaching. Compared with the traditional teaching mode, the theoretical knowledge and clinical operation skills of medical students under the PBL teaching mode are improved by 13%, Autonomous learning ability, communication ability and creative thinking ability have also been relatively improved.